2018
DOI: 10.3758/s13415-018-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Facing temptation: The neural correlates of gambling availability during sports picture exposure

Abstract: Nowadays, sports betting has become increasingly available and easy to engage in. Here we examined the neural responses to stimuli that represent sporting events available for betting as compared to sporting events without a gambling opportunity. We used a cue exposure task in which football (soccer) fans (N = 42) viewed cues depicting scheduled football games that would occur shortly after the scanning session. In the "betting" condition, participants were instructed to choose, at the end of each block, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 77 publications
(82 reference statements)
1
15
0
1
Order By: Relevance
“…This finding was thought to be an indicator of higher engagement of stimulus recognition and the perceptual saliency process for the stimuli associated with reward, and the insula was proposed as a modulator region in recognition of stimuli with or without reward value. 31 Similarly, in conditions with negative and positive emotional valance as in our study design, the dACC may play the critical modulating role of the insula for the recognition of the different types of stimuli that are emotionally laden rather than carrying a reward value.…”
Section: Clinical Neurosciencesmentioning
confidence: 80%
“…This finding was thought to be an indicator of higher engagement of stimulus recognition and the perceptual saliency process for the stimuli associated with reward, and the insula was proposed as a modulator region in recognition of stimuli with or without reward value. 31 Similarly, in conditions with negative and positive emotional valance as in our study design, the dACC may play the critical modulating role of the insula for the recognition of the different types of stimuli that are emotionally laden rather than carrying a reward value.…”
Section: Clinical Neurosciencesmentioning
confidence: 80%
“…Research is thus warranted to extend previous neuroimaging work on gambling cue reactivity by examining how the prospect of actual betting impacts specific brain pathways. Initial strides toward this research direction have been taken by Brevers and colleagues [••96]. These authors reported, through the use of an fMRI cue exposure task (adapted from a food cue reactivity study; [97]), that thinking about a sporting event with the intention of gambling on the outcome, compared with thinking about it with the mere intention of watching it, triggers higher prefrontal, insular and striatal activations in a sample of football (soccer) fans.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported, through the use of an fMRI cue exposure task (adapted from a food cue reactivity study; [97]), that thinking about a sporting event with the intention of gambling on the outcome, compared with thinking about it with the mere intention of watching it, triggers higher prefrontal, insular and striatal activations in a sample of football (soccer) fans. Importantly, Brevers et al [••96] used ecological cues (i.e. football games that were occurring in real life in the days following the scan, with the logos and names of the two teams facing each other), and manipulated gambling reward availability/expectancy (participants received additional money if the team they chose to bet on eventually won the game).…”
Section: Introductionmentioning
confidence: 99%
“…Initial strides towards this objective have been taken by neuroimaging research on cue–reactivity . Specifically, a recent functional magnetic resonance imaging study has shown that the brain processes information about sporting cues differently, depending on whether sports fans think about a sporting event with the intention of gambling on the outcome or think about it with the intention of merely watching it . From the standpoint of the present commentary, the examination of sports betting, cue–reactivity should greatly benefit from a multi‐level approach, featuring eye‐tracking measurements.…”
mentioning
confidence: 99%
“…individuals exposed to visual stimuli on a computer screen). Secondly, because every sports fan can express a degree of confidence in the result of a forthcoming sports event , research should be able to grasp how eye movements are modulated by the level of interest and by the weighing process of deliberative thought towards sports betting cues. Thirdly, in contrast to sexual activity, food, buying, or consuming psychoactive substances, sports betting (and gambling per se ) does not show sensory‐specific satiety effects (i.e.…”
mentioning
confidence: 99%